2004
DOI: 10.1177/1052562903260808
|View full text |Cite
|
Sign up to set email alerts
|

Active Learning Facilitated by Using a Game-Show Format or Who Doesn’t Want to be a Millionaire?

Abstract: University faculty are increasingly called on to be less of a sage on the stage and more a guide on the side. This discussion introduces the underlying philosophy and assumptions of active learning theory. With this shift in pedagogical philosophy, there has been an increasing call for tools that actively engage students in the learning process. A game-show format is suggested as an effective classroom tool for active learning. Examples are given that draw on the television shows Who Wants to be a Millionaire?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 7 publications
(6 reference statements)
0
38
0
2
Order By: Relevance
“…During traditional lectures, students are generally passive (Dorestanni, 2005;Felder & Brent, 2004;Steward-Wingfield & Black, 2005), and consequently, information received passively with no attendant action is not readily retained in long-term memory (van Eynde & Spencer, 1988). Research also suggests that students learn best when they take an active role in learning through discussion, practicing, games, and applying concepts and ideas (Chickering & Gamson, 1987;Cortright, Collins, & DiCarlo, 2005;Mierson, 1999;Sarason & Banbury, 2004). A recent study involving engineering students found that active learners achieved greater levels of learning and motivation than did their passive peers (Gonzalez, Rodriguez, Olmos, Borham, & Garcia, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…During traditional lectures, students are generally passive (Dorestanni, 2005;Felder & Brent, 2004;Steward-Wingfield & Black, 2005), and consequently, information received passively with no attendant action is not readily retained in long-term memory (van Eynde & Spencer, 1988). Research also suggests that students learn best when they take an active role in learning through discussion, practicing, games, and applying concepts and ideas (Chickering & Gamson, 1987;Cortright, Collins, & DiCarlo, 2005;Mierson, 1999;Sarason & Banbury, 2004). A recent study involving engineering students found that active learners achieved greater levels of learning and motivation than did their passive peers (Gonzalez, Rodriguez, Olmos, Borham, & Garcia, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The goal of this research is to achieve better understanding for student attitudes toward use platform as learning resources format at UGr, in addition, in this research paper investigative the effect use platform as learning resources on gender, owning a PC, and access to the internet. Numerous studies have demonstrated that a student's active involvement in the learning process enhances learning, a process often referred to as active learning (Benek-Rivera & Matthews, 2004;Sarason & Banbury, 2004). Simply stated, active learning involves "instructional activities involving students in doing things and thinking about what they are doing" (Bonwell & Eisen, 1991, p. 5).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These include improved classroom interaction, improved student learning, improved motivation, better retention of material and better attendance (Blasco-Arcas, et al, 2013, Bruff, 2009, Caldwell, 2007, Moredich and Moore, 2007, Rowlett, 2010. In addition, action learning activities and classroom assessment techniques (Angelo and Cross, 1993) are easier implemented through the use of SRSs (Sarason andBanbury, 2004, McLoone et al, 2015).…”
Section: Introductionmentioning
confidence: 99%